Human milk can neutralize Coxsackievirus B4 in vitro. Issue 5 (13th February 2013) - Sane, F.; Alidjinou, E.K.; Kacet, N.; Moukassa, D.; Charlet, C.; Ebatetou‐Ataboho, E.; Ngoulou, W.; Badia‐Boungou, F.; Romond, M.B.; Hober, D.
Abstract The role of enteroviruses in type 1 diabetes has long been suspected. A lower risk of type 1 diabetes is associated with breastfeeding, which could be due to a protective effect against enteroviruses. The neutralizing activity of breast milk against CVB4, a representative of enteroviruses was investigated in this study in vitro. Breast milk was cytotoxic to Hep‐2 cells up to a dilution of 1/32, whereas the aqueous fraction obtained after centrifugation was not cytotoxic; although it inhibited the cytopathic effect of CVB4 on Hep‐2 cell monolayers. The anti‐CVB4 neutralizing activity of aqueous fractions of breast milk from 49 donors living in Northern France and 15 donors living in Congo, where enteroviral infections are more prevalent, were determined. The levels of colostrum activity expressed as titre ranged from <2 to 32 in 36% of the donors from France whereas they were >128 in every donor from Congo. Pasteurized colostrum had a lower anti‐CVB4 activity compared to fresh samples (P < 0.0001, n = 49). The treatment of colostrum samples with jacalin‐coated beads that bind specifically to human IgA, showed that IgA plays a role in anti‐CVB4 activity. There was no correlation between the neutralizing activities of breast milk and serum (P = 0.37, n = 25). The current study showed that the variations in anti‐CVB4 activity in breast milk can be attributed to environmental and living conditions. Whether a low protective activity of breast milk against enteroviruses expose newborns to a higher risk of type 1 diabetes deserves further investigation. J. Med. Virol. 85:880–887, 2013. © 2013 Wiley Periodicals, Inc.